Persons Living With HIV in the United States: Fewer Than We Thought. (15th August 2016) - Xia, Qiang; Braunstein, Sarah L.; Wiewel, Ellen W.; Eavey, Joanna J.; Shepard, Colin W.; Torian, Lucia V.
Abstract : Objectives: To estimate the number of persons living with HIV (PLWH) in the United States and to describe their care status. Methods: Estimates of diagnosed PLWH in New York City and other 19 jurisdictions based on HIV case reporting were compared with those based on HIV laboratory reporting. A revised HIV care continuum was constructed based on previously published data. Results: The estimate of PLWH based on HIV case reporting was 25.6% higher than that based on HIV laboratory reporting data in New York City. There were 819, 200 PLWH in the United States at the end of 2011 (plausible range: 809, 800–828, 800), of whom 86% were diagnosed, 72% were retained in care (≥1 care visit in 2011), 68% were on antiretroviral therapy, and 55% were virally suppressed (⩽200 copies/mL). Conclusions: The current method based on HIV case reporting may have overestimated PLWH in the United States. While we continue cleaning HIV case reporting data to improve its quality, we should take the opportunity to use comprehensive HIV laboratory reporting data to estimate PLWH at both the national and local levels.